Risk Factors for Stunting at The Lurasik Health Center - Nopala, Eleonora Edeltrudis; Picauly, Intje; Talahatu, Anna H (Timorese Journal of Public Health, 2021)
Stunting is a condition of failure to thrive in children under five years old (infants under five years old) due to chronic malnutrition so that the child is too short for his age. This study aims to determine the factors that influence the incidence of stunting in the Lurasik Health Center Work area, North Biboki District, North Central Timor Regency. This type of research is an analytic survey with a case-control study design. The sample of the study was 148 toddlers who were divided into 74 case samples and 74 control samples. The use of data analysis was univariate, bivariate, and multivariate analysis with statistical tests of simple logistic regression and multiple logistic regression. The results of this study indicate that the factor which influences stunting was a history of infectious disease (p= 0.008), energy adequacy level (p= 0.000), protein adequacy level (p = 0.000), history of exclusive breastfeeding (p= 0.000), level of parental income (p= 0.031), while the factor that did not affect the incidence of stunting was level of mother’s work (p= 0.869). The dominant factor which most influence the stunting was the history of gave breastfeeding, the level of energy sufficiency and the level of protein adequacy. It is hoped that with the factors that influence the incidence of stunting in toddlers in the working area of ​​the Lurasik Health Center, it can add information to the public so that stunting prevention is further improved